An exploratory statistical cusp catastrophe model for the prediction of the effect of special education teachers’ emotional intelligence on their burnout - Antoniou, Alexandros-Stamatios; Charitaki, Garyfalia; Pavlidou, Kyriaki; Alevriadou, Anastasia (Frontiers in Education, 2025)
In the present research, the relationship between emotional intelligence and burnout was investigated in a sample of Greek special education teachers. The cusp catastrophe model was used for the statistical analysis. Based on the analysis, emotional intelligence was negatively correlated with burnout. Surprisingly, this negative relationship was reversed when the increase in the level of emotional intelligence exceeded a certain point. There seems to be a fragile balance between caring and caring too much. Teachers who cannot regulate their sentimentality can be overwhelmed by emotions and become prone to stress and burnout. The cusp catastrophe model managed to describe that phenomenon more satisfactorily than the linear and quadratic models tested. According to the other analysis results, factors such as mental resilience and self-efficacy had a negative relationship with burnout. Practical implications such as emotional intelligence training and self-focus wellbeing were discussed.